Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How would I work out a limit of the form:

$$\lim_{x\to 0}\;(1+x)^{1/x}$$

I know these types of limits have a solution based on $e$ but how do I find this solution?

share|improve this question
3  
The limit is $1$. $1^0$ is not an indeterminate form. If you asked for $\lim_{x\to 0} (1+x)^{1/x}$, that would be a different story, –  Grumpy Parsnip Aug 23 '11 at 20:43
    
$(1+0)^0 \to 1^0 \to 1$, no indeterminancy here. The indeterminancy appears in limits of the form $1^\infty$, eg $\lim\limits_{x\to0}(1 + x)^{1/x}$ –  leonbloy Aug 23 '11 at 20:43
    
I asked the wrong question, I'm sorry. You were guessing for the right question.. could you provide me with a solution now? –  Mats Aug 23 '11 at 20:48
add comment

5 Answers 5

up vote 5 down vote accepted

Hint:

The functions $y = \log x$ and $y = e^x$ are continuous, and continuous functions respect limits: $$ \lim_{n \to \infty} f(g(n)) = f\left( \lim_{n \to \infty} g(n) \right), $$ for all continuous functions $f$, whenever $\displaystyle\lim_{n \to \infty} g(n)$ exists. Let $$L=\lim\limits_{x\to 0}(1+x)^{1/x}$$ be the limit which you to wish to find. Instead of finding $L$ directly, try on your own to find $\ln(L)$.

share|improve this answer
    
This is actually the best answer! You take a nice teaching approach! –  Mats Aug 23 '11 at 21:24
    
@Mats: Thank you. Considering you said you had an exam tomorrow, I figured I'd explain the more general strategy :) –  JavaMan Aug 23 '11 at 23:51
add comment

$\lim\limits_{x \rightarrow 0}\exp (x\ln (1+x))=\exp(\lim\limits_{x \rightarrow 0}(x\ln(1+x)))=\exp(0)=1$.

$\lim\limits_{ x \rightarrow 0}\exp ( \frac{\ln (1+x)}{x})=\exp(\lim\limits_{x \rightarrow 0}(\frac{\ln(1+x)}{x}))=\exp(1)=e$. Use L'Hospital.. to see $\lim\limits_{x \rightarrow 0}\frac{\ln(1+x)}{x}=1$

share|improve this answer
    
With exp(x) do you mean $e^x$? –  Mats Aug 23 '11 at 21:01
    
@Mats:$\quad$yes! –  Quixotic Aug 23 '11 at 21:06
add comment

Try writing this as $$ \lim_{n\to\infty}\left(1+\frac{1}{n}\right)^n $$ The binomial theorem may be of some help then.

Another way of looking at this is taking logs and using L'Hospital $$ \log\left(\lim_{x\to0}(1+x)^{1/x}\right)=\lim_{x\to0}\frac{\log(1+x)}{x} $$

share|improve this answer
    
This is not the right solution .. It was something with putting the whole limit as a power of $e$ .. but I forgot the correct solution method. –  Mats Aug 23 '11 at 20:54
    
@Mats: I added another approach. However, both yield the same answer, but in different forms. –  robjohn Aug 23 '11 at 20:56
3  
@Mats: The first suggested solution is fine, it just requires some work. There is no universal "right solution"..... –  Eric Naslund Aug 23 '11 at 20:59
    
@Eric: The Binomial Theorem can produce a series for the limit that converges pretty fast. The limit is usually the definition for $e$, and if that is the case, all that is left is to compute the value. –  robjohn Aug 23 '11 at 20:59
1  
@Mats:This is a correct solution,put $\frac{1}{x} = n$ then as $x\to 0 \Rightarrow n\to\infty$ after this expand using multinomial/binomial theorem with rational index,arranging the terms and substituting the limit you will get this $1+\frac{1}{1!}+\frac{1}{2!}+\frac{1}{3!}+\frac{1}{4!}+\cdots = e$ –  Quixotic Aug 23 '11 at 21:02
show 3 more comments

If we use the substitution $x=\frac{1}{y}$, since $\lim_{x\rightarrow 0}x=\lim_{y\rightarrow \infty }\frac{1}{y}$, we get

$$\lim_{x\rightarrow 0}\left( 1+x\right) ^{1/x}=\lim_{y\rightarrow \infty }\left( 1+\frac{1}{y}\right) ^{y}=e,$$

which uses the result

$$\lim_{n\rightarrow \infty}\left( 1+\frac{1}{n}\right) ^{n}=e.$$

share|improve this answer
    
@AidenStrydom See last formula of your answer. –  Américo Tavares Sep 10 '12 at 7:21
    
Dear sir - my apologies i miss read your answer. Please forgive me –  Aiden Strydom Sep 10 '12 at 8:09
add comment

Sorry for uploading the image - i am new and have yet to figure out how to mark up the math

The first line assumes you know that if f(x) = ln(x) then f'(1) = (ln(x+h) - ln(x)) / h

ps f'(1) = 1 enter image description here

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.